The changing generosity of the UK state pension system to the self-employed - Mihai Alexandru Codreanu; Rowena Crawford; Jonathan Cribb; Carl Emmerson (Institute for Fiscal Studies (IFS), 2020)
Recent years have seen increasing concerns in many developed countries over 'the changing nature of work'. For example, in the United Kingdom, the Taylor Review notes that only 60% of workers are permanent employees. In the United States, a recent review by Mas and Pallais (2020) found that alternative working arrangements such as solo self-employment, zero hours contracts, agency work, independent contractors, and jobs in the gig economy are now more prevalent than 'traditional' jobs. The rising numbers of the self-employed are one of the drivers of these changes. Data from the Bank of England (2018) and the Office for National Statistics (2018a, b) suggest that in recent years the proportion of the UK workforce working for their own business reached its highest level since at least 1854. As shown in Figure 1.1, in the past 20 years the proportion has increased by 3 ppt. With an increasing employment rate and growing population over this period, the numbers of individuals who declare that they are working for their own business as their main economic activity has increased substantially from 3.2 million in 2000 Q2 to 4.8 million in 2018 Q2.
Keywords: 330; Rentenpolitik; Arbeitsverhalten; Rentenreform; Selbstständige; Großbritannien